Empirical Study On, “Chracteristics Of Agripreneurship In Amhara Region, Ethiopia” - Nachimuthu, Dr.Kavitha; Melesse, Mr.Birhanu; Derso, Mr.Beyene (International Journal of Scientific Research and Management (IJSRM), 2018)
Agripreneurship rotate farm into an agribusiness. Agribusiness plays very essential role to re defining agricultural sector in Ethiopia. It make more advantageous venture can lead to economic self-sufficiency which attracts rural people in the present scenario. Agripreneurship provides employment opportunities, income generation, alleviating poverty, food security and rural livelihood in the development aspects. Most of the farmers lack in access of agricultural raw materials, financial assistance, marketing arrangements, accessing new technologies and advisory services for commercial farming. ‘Agripreneurs’ can transform Ethiopian agriculture sector to meet the challenges in the global world. This paper mainly focused on the importance of Agripreneurship and socio cultural background in Ethiopia